Boron Nitride Nanoparticles with High Specific Surface Area: Preparation by a Calcination Method and Application in Epoxy Resin - Wu, Xiang-feng; Zhao, Ze-hua; Sun, Yang; Li, Hui; Wang, Yi-jin; Zhang, Chen-xu; Gong, Xiao-dong; Wang, Yu-duan; Yang, Xin-yue; Liu, Yu (Journal of inorganic and organometallic polymers and materials, 2017)
Boron nitride nanoparticles were prepared in a muffle furnace at 1000 °C by using commercial available boron nitride flakes and sodium chloride as raw materials. The structure, functional groups, morphology and specific surface area of the as-prepared samples were characterized by X-ray diffracmeter, fourier-transform infrared spectrometer, transmission electron microscope and accelerated surface area/porosimetry system, respectively. In order to evaluate the properties of the as-prepared products, they were mixed with epoxy resin to fabricate polymer-based composites. Experimental results showed that the average size and specific surface area of the as-prepared nanoparticles were about 20 nm and 895.7 m 2 /g. Moreover, the as-prepared nanoparticles could improve the tensile strength and elongation at break of the epoxy matrix. Both of them were first increased and then decreased with increasing the usage amount of the as-prepared nanoparticles. When the usage amount of the boron nitride nanoparticles was 0.4 wt%, the tensile strength and elongation at break of the composites reached to 71.4 MPa and 22.1%, which were the maximum values of the composites, respectivley. They were increased by 137 and 146% more than those of pure epoxy resin. In addition, the as-prepared fillers could accelerate the solidification of the matrix.